Pengaruh Financial Technology dan Gaya Hidup Terhadap Perilaku Keuangan Generasi Z di Kabupaten Bandung - Rukoyah, Siti; Susilawati (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The purpose of this study is to examine how financial technology and lifestyle affect the financial behavior Generation Z group in Bandung Regency. This research applies a quantitative approach by utilizing two data sources, namely primary data and secondary data. Primary data collection was carried out through a questionnaire instrument distributed to research respondents through Google Forms to Generation Z in Bandung Regency. The sampling method was carried out through accidental sampling techniques, while the determination of the sample size was based on the calculation of the Slovin formula which resulted in 100 representative respondents. This study found that financial technology has a positive influence with a validated significance level on the financial behavior of Generation Z in Bandung Regency, lifestyle has a positive influence with a validated significance level on the financial behavior of Generation Z in Bandung Regency, and simultaneous testing confirmed that financial technology and lifestyle contribute positively with a validated significance level in shaping the financial behavior of Generation Z in Bandung Regency.